2020
DOI: 10.3389/fchem.2020.00759
|View full text |Cite
|
Sign up to set email alerts
|

Functional Up-Conversion Nanoparticle-Based Immunochromatography Assay for Simultaneous and Sensitive Detection of Residues of Four Tetracycline Antibiotics in Milk

Abstract: An ultrahigh-sensitivity lateral flow immunochromatography (LFIC) assay based on up-converting nanoparticles (UCNPs) was developed to carry out a multi-residue detection of tetracycline in milk. The sensitivity of the immunoassay was greatly improved by the use of a broad-spectrum monoclonal antibody attached to UCNPs to form a signal probe. Under the optimal conditions, the UCNP-LFIC assay enabled sensitive detection of tetracycline (TC) as well as of oxytetracycline (OTC), chlortetracycline (CTC), and doxycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…38 With a conjugated system and abundant amino groups, CTC can be a candidate to attach to BSA by EDC chemistry and can be characterized by a UV−vis spectrophotometer. 39 Furthermore, the reports from Taheran et al 40 and Parolo et al 41 suggested CTC possessed net negative charges around pH 7, enhancing electrostatic repulsion and restraining the adsorption between CTC and a negatively charged material. According to their work, the interaction between negatively charged CTC and negatively charged BSA-blocked silica colloidal crystal (SCC) film was mainly forced by electrostatic repulsion at pH 7.2, the condition used in our experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 With a conjugated system and abundant amino groups, CTC can be a candidate to attach to BSA by EDC chemistry and can be characterized by a UV−vis spectrophotometer. 39 Furthermore, the reports from Taheran et al 40 and Parolo et al 41 suggested CTC possessed net negative charges around pH 7, enhancing electrostatic repulsion and restraining the adsorption between CTC and a negatively charged material. According to their work, the interaction between negatively charged CTC and negatively charged BSA-blocked silica colloidal crystal (SCC) film was mainly forced by electrostatic repulsion at pH 7.2, the condition used in our experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CTC is widely used in livestock, poultry, and aquatic organisms with the advantage of economic savings . With a conjugated system and abundant amino groups, CTC can be a candidate to attach to BSA by EDC chemistry and can be characterized by a UV–vis spectrophotometer . Furthermore, the reports from Taheran et al and Parolo et al suggested CTC possessed net negative charges around pH 7, enhancing electrostatic repulsion and restraining the adsorption between CTC and a negatively charged material.…”
Section: Introductionmentioning
confidence: 99%
“…A novel method of membrane detection, FICA, combines chromatographic chromatography with immunological methods (Pyo & Yoo, 2012). The advantages of low cost, ease of use, quick reaction, and high sensitivity have allowed this technique to be widely used in food and drug analysis (Wang et al, 2016; Xu et al, 2020; Zhang et al, 2020). FICA determination offers a practical and reliable method for clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A lateral flow immunoassay (LFIA), which combines chromatography technology with conventional immunoassay and nanomaterials, is considered the most attractive point-of-care testing device, because it exhibits several advantages, including simple technical requirements, rapid detection capability, portability, affordability, high detection accuracy, and high efficiency [ 25 ]. LFIAs have been widely applied in detecting pesticide [ 26 , 27 ] and veterinary drugs residues [ 28 , 29 ], toxicants [ 30 , 31 , 32 ], pathogens [ 32 , 33 ], various diseases biomarkers, as well as SARS-CoV-2 antigen/antibody [ 34 , 35 ]. Usually, the results of a LFIA are presented with the test and control lines showing the same color, resulting in it not being easy for users to discern the locations of test and control zones.…”
Section: Introductionmentioning
confidence: 99%